Anxiety-related concussion perceptions of collegiate athletes. Issue 12 (December 2021) - Beidler, Erica; Eagle, Shawn; Wallace, Jessica; Anderson, Morgan; Schmitt, Ara J.; O'Connor, Siobhan; Kontos, Anthony P.
Abstract: Objectives: The purpose of this study was to identify collegiate athletes' anxiety-related concussion perceptions and examine factors that may be related to increased anxiety injury beliefs. Design: Cross-sectional study. Methods: Male and female Division I, II and III NCAA collegiate athletes ( n  = 482) completed a 10- to 15-minute survey examining their demographics, diagnosed concussion history, concussion knowledge, and public media sources they have previously acquired concussion information from. The survey also included the Perceptions of Concussion Inventory for Athletes (PCI-A) which results in six outcome variables (anxiety, effects, control, clarity, treatment, and symptom variability). Univariable and a backward stepwise multivariable logistic regression model were utilized to identify variables that were associated with greater (above median) negative anxiety-related concussion perception scores. Results: Collegiate athletes displayed moderate anxiety-related concussion perceptions (12.8 ± 3.2; scores ranged from 4 — low anxiety to 20 — high anxiety). The majority of participants reported that concussions are upsetting to them (60.7%), with a sizable proportion being worried (46.7%), fearful (40.7%), or anxious (25.0%) about sustaining a concussion. In the multivariable regression, higher perception that concussions have long-term effects (OR = 2.72; 95% CI: 1.79–4.12), greater beliefs of internal control to influence concussion outcomes (OR = 1.78; 95% CI: 1.15–2.75), and female sex (OR = 1.77; 95% CI: 1.15–2.71) were associated with higher anxiety beliefs. Conclusions: This study for the first time establishes that negative, anxiety-related perceptions about concussions are prevalent in a collegiate athlete population. Addressing these perceptions through evidence-based, educational and management initiatives, such as highlighting that concussions are treatable and most do not result in long-term negative consequences with early diagnosis and proper management, are critical to improve emotions surrounding concussion. This may be particularly important for female athletes in this population.